The role of social determinant of health in couples’ infertility - Baybordi, Elaheh (Social Determinants of Health, 2019)
Background: Infertility is a medical and social status that can cause social, emotional and psychological disturbances in infertile couples. The purpose of this study was to determine the role of social determinants of health among infertile couples. Methods: This descriptive cross-sectional study was carried out in 6 months. The participants in this study were infertile couples referring to Tabriz Jahade Daneshgahi Infertility Treatment Center which is one of the referral centers for infertility treatment in northwestern Iran. Self-administered questionnaire with closed questions was provided to the participants using a Likert scale to collect data. The questionnaire included demographic data including age, sex, occupation, place of living, income, history of the cause and duration of infertility and social protection of individuals. Results: The total number of participants was 205, with a mean age of 6.89±33.78 years. In examining the cause of infertility, 66 (39.1%) had male infertility, 48 (28.4%) had female infertility, 54 (32%) had both female and male, and one case (0.6%) with an unknown cause. In different levels of education, the male factor as a cause of infertility in each level was more prevalent, which showed a significant difference only at the level of the bachelor’s degree. In examining the degree of satisfaction with utilizing existing opportunities and facilities in a society based on the income of the participants in the study; all those with the lowest degree of satisfaction belong to the lowest income group of the community. Conclusion: Social factors influencing health have greatly influenced the incidence and cause of couples’ infertility who want to have a child.